Assessment of the Impact Of Hormonal Correction of Subclinical Hypothyroidism in Migraine on Patients' Quality of Life and Daily Work Activity (Eurasian Medical Research Periodical, 2022)
Migraine is a common disease, accounting for one-third of all neurological diseases [6]. About 90% of people with migraines are bothered by moderate to severe headaches. Migraine is diagnosed in 90% of patients who present with a headache for the first time [3]. Three-quarters of patients experience a decrease in daily activity during a headache attack, and one-third require a bed rest [7]. Several clinical and epidemiological studies have reported that migraine is a topical disease due to the low effectiveness of migraine treatment [1, 2, 4, 5].